2021
DOI: 10.1007/s10098-021-02242-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of hot air drying and microwave drying for dewatered sludge

Abstract: Large amounts of sludge are generated from wastewater treatment in seafood processing industries.Most of the dewatered sludge in Thailand is not utilized and disposed by land lling. The dried sludge utilization as refuse-derived fuel (RDF) is an alternative solution due to the gross calori c value (GCV), which is greater than 21.9 MJ/kg. However, the key obstacle is its high moisture content of 87.4% (wet basis). Therefore, drying methods using hot air and microwave techniques were investigated for preparing d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The results showed that the number of macropores increased gradually with the increase in the particle size of soil aggregates, which was consistent with previous studies. Then, the method of hot air drying [10,11] was used to blow hot air into the wet soil to…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results showed that the number of macropores increased gradually with the increase in the particle size of soil aggregates, which was consistent with previous studies. Then, the method of hot air drying [10,11] was used to blow hot air into the wet soil to…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the number of macropores increased gradually with the increase in the particle size of soil aggregates, which was consistent with previous studies. Then, the method of hot air drying [10,11] was used to blow hot air into the wet soil to solve the problem of excessive moisture in the soil pores. The study found that hot air would produce different forms of heat flow under different sized pore structures, thus producing different heat and mass transfer rules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been applied in ginger drying to determine the appropriate microwave power and drying temperature for the final product (Zeng et al, 2023). Similarly, microwave drying was applied for dewatered sludge, and it was found that the application of microwaves reduced the drying time by at least 37.5% compared to using hot air (Wulyapash et al, 2022). In addition to quality prospectus, concerns that producers are preoccupied with are energy usage that influences drying costs.…”
Section: Introductionmentioning
confidence: 99%